Passively Q-Switched Mode-Locked Tm,Ho:CaYAlO4 Laser Based on Double-Walled Carbon Nanotube Saturable Absorber - Zhang, Yani; Ling, Weijun; Qiao, Dun; Sun, Rui; Chen, Chen (Frontiers in Physics, 2020)
A passively Q-switched mode-locked (QML) operation in Tm, Ho: CaYAlO4 bulk laser was demonstrated experimentally by employing double wall carbon nanotube (DWCNTs) as a saturable absorber. The laser is pumped by a self-made wavelength tunable Ti: sapphire laser, and the pump threshold of Tm, Ho: CaYAlO4 laser was measured as 677 mW by using transmittance of 1.5% output coupler. A stable Q-switched mode-locked operation state was achieved when the absorption pumping power reached 1958 mW. And when the pumping power reached 2.6 W, a maximum output power was 64 mw with central wavelength of 2085 nm, the corresponding repetition frequency of mode-locked pulse was 98.04 MHz, and the modulation depth in Q-switching envelopes is close to 100%.